Analysis of Custody Rights for Children Whose Parents are Divorced - Ismawati Septiningsih (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Problems that often arise as a result of divorce between married couples who already have children are related to child custody. Each husband and wife has the right to apply for custody of their child by submitting an application to the court. This research will answer problems related to child custody regulations after the parents divorce and the legal consequences for children whose parents divorce. This article was written using normative legal research with a legislative approach. The results of this research are that child custody is adjusted to the condition of the child or father or mother and the one that is most beneficial for the child's welfare is chosen, and the legal consequences for children whose parents are divorced are that the parents' obligation to educate their children is not lost.